Charybdis glaucophylla (Asparagaceae), a new species from Sardinia - Bacchetta, Gianluigi; Brullo, Salvatore; D’emerico, Saverio; Pontecorvo, Cristiano; Salmeri, Cristina (Phytotaxa, 2012)
Charybdis glaucophylla (Asparagaceae), a new species from Sardinia, is described and illustrated. It is a diploid species with 2n = 20 chromosomes growing along the rocky coast, sandy dunes and mountain top in the south-western part of the island. Within the genus, this species results taxonomically well isolated and differentiated due to relevant morphological and phenological features, such as the leaves wide and short, very rigid and glaucous-pruinose, as well as the very late foliation (winter). It shows only some relationships with C. pancration for the whitish bulb tunics and the diploid chromosome complement, and with C. maura and C. aphylla due to the glaucous leaves.